PENGARUH PRAKTIK KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PESERTA DIDIK KELAS XII PEMASARAN SMKN 8 PONTIANAK - Maimuna, Maimuna; Syahrudin, Husni; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The goals of this research are to determine: 1) the prevalence of entrepreneurial practices in the business centers of class XII students majoring in marketing at SMK Negeri 8 Pontianak; 2) the level of entrepreneurial interest among these students; and 3) the extent to which exposure to entrepreneurial practices influences students' interest in entrepreneurship. The strategy employs a quantitative methodology based on correlation. A representative sample of the entire student body (n=94) was taken. Linear regression is used as the method for analyzing the data. According to the findings, 1) a large majority (74.40%) of class XII marketing majors have a favorable view of entrepreneurial practices. 2) Class XII students who plan to study marketing fall into the "high" category for their level of interest in starting their own businesses, at 72,98 percent. Interest in starting a business is influenced by third-party examples of entrepreneurship. 3) Class XII marketing students at SMK Negeri 8 in Pontianak saw a 27.3% increase in their enthusiasm for entrepreneurship as a direct result of their exposure to entrepreneurial activities. SPSS 25's calculations show a significance of 0.000 0.05, dismissing the null hypothesis (H0), and accepting the alternative (Ha). Thus, it can be concluded that class XII students at SMK Negeri 8 Pontianak who are majoring in marketing are influenced by the entrepreneurial practices of the school business center